Combined effects of double porous layers and nanofluids on the performance of confined single and multi-jet impingement heat transfer - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Taylor & Francis Inc, 2022)
In this study, nanofluid jet impingement cooling performance with single and multiple jets are analyzed under the impacts of using double porous layers with finite element method (FEM). The numerical study is performed by using different values of pertinent parameters as: Re number (100 <= Re <= 300), permeability of the porous zones (10(-4) <= Da1 <= 10(-1) and 10(-4) <= Da2 <= 10(-1)), second porous layer height (0.1H <= d2 <= 0.5H), distance between the porous layers (0.1H <= h <= 0.5H), solid volume fraction (0 <= phi <= 3%), and particle diameter (20nm <= dp <= 80nm). Discrepancies between the single and multiple jet configurations become higher for Re numbers while at Re = 300, the average heat transfer (HT) is 31% for multiple jet case. The presence of the double porous layers significantly affects the convective HT performance and the highest impact is observed by varying the permeability of the porous layers. When the lowest and highest permeability of the lower layer are compared, there is 119% variation in the average Nu for multi-jet (MJ) case and this value is 84.5% for single jet (SJ) case. When varying the permeability of the upper porous layer, the highest HT rate is achieved at Darcy number of 10(-3) while 32% higher Nu is obtained for MJ case as compared to SJ case. There is slight impact of the distance between the porous layers on the fluid flow and HT while varying the height of the upper layer results in 8.9% variation in the average Nu number. Inclusion of the nanoparticle (NP) further improves the average Nu by about 11% for single and multiple jet cases at the highest solid volume fraction while the impact of NP size is slight.
Keywords: Finite element method; multiple jet; nanofluid; porous layer